TINGKAT PENGANGGURAN TERBUKA DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA:STUDI KASUS PROVINSI KEPULAUAN RIAU - mochamad ridwan ridwan (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2022)
This study aims to analyze the development of the open unemployment rate in Riau Province and the two factors that influence it, namely regional economic growth and regional minimum wage levels. The type of research used in this research is explanatory research. The type of data collected includes secondary data (as the main data). The analytical method used is a quantitative descriptive method. The results of the study show that the results of the test show that partially economic growth has a significant and negative effect on the open unemployment rate in the Riau Archipelago Province, with a regression coefficient of 0.481291 percent; while the provincial minimum wage (UMP) has a significant and negative effect on the open unemployment rate in the Riau Archipelago Province, with a regression coefficient of 0.777358 percent. Simultaneously, economic growth and the provincial minimum wage (UMP) have a significant effect on the open unemployment rate in the Riau Archipelago Province.